Validation of same-day bowel preparation regimen using 4L polyethylene glycol: Comparison of morning and afternoon colonoscopy. Issue 37 (September 2018) - Huh, Cheal Wung; Gweon, Tae-Geun; Seo, Myeongsook; Ji, Jeong Seon; Kim, Byung-Wook; Choi, Hwang
Abstract : Abstract: A split-dose regimen is the recommended method of bowel preparation for colonoscopy. However, for colonoscopy performed in the afternoon, same-day preparation is recommended rather than a split-dose regimen. No study has compared the efficacy of same-day bowel-cleansing for morning colonoscopy (MC) and afternoon colonoscopy (AC). The aims of this study were to evaluate the bowel-cleansing efficacy, adverse events, and patient tolerability of same-day bowel preparation for colonoscopy using 4L polyethylene glycol (PEG). The medical records of consecutive patients who underwent colonoscopy at our healthcare center over 3 months were retrospectively reviewed. Colonoscopy was performed between 10:00 and 16:00. Study subjects were assigned to the MC or AC group according to their colonoscopy start time (MC group, before 12:00; AC group, after 12:00). Study subjects were instructed to drink 500-mL PEG every 15 minutes. In the MC group, bowel cleansing was started at 05:00 and finished at 07:00. For the AC group, 2L PEG was consumed from 07:00, and the remaining 2L PEG was started 3 hours before colonoscopy. The composite safety profile included vital signs, laboratory test results, and questionnaire findings. Laboratory testing of subjects and completion of the questionnaire were performed before colonoscopy. The questionnaire asked about adverse events and tolerability of the bowel cleansing regimen. Bowel-cleansing efficacy was assessed using the Boston bowel preparation scale (BBPS). Bowel-cleansing efficacy, tolerability, and safety profile were compared between the 2 groups. Two hundred and ninety-one subjects were included (MC group, 169; AC group, 122).The BBPS did not differ between the 2 groups (7.3 ± 0.8 vs. 7.3 ± 0.8, P  = .68). There were no instances of electrolyte imbalance or hemodynamic instability in either group. The tolerability of the bowel-cleansing regimen did not differ between the 2 groups ( P  = .59). The bowel-cleansing efficacy, safety profile, and patient tolerability of MC and AC were comparable. A same-day dose of 4L PEG is a feasible bowel preparation method.